A global history of the financial crash of 2007-2010 - Lybeck, Johan A. 1944- (Cambridge University Press, 2008)
We have just experienced the worst financial crash the world has seen since the Great Depression of the 1930s. While real economies in general did not crash as they did in the 1930s, the financial parts of the economy certainly did, or, at least, came very close to doing so. Hundreds of banks in the United States and Europe have been closed by their supervisory authorities, forcibly merged with stronger partners, nationalized or recapitalized with the tax payers' money. Banks and insurance companies had, by mid 2010, already written off some 2000 billion dollars in credit write-downs on loans and securities. In this book, Johan Lybeck draws on his experience as both an academic economist and a professional banker to present a detailed yet non-technical analysis of the crash. He describes how the crisis began in early 2007, explains why it happened and shows how it compares to earlier financial crises